2021
DOI: 10.1093/sleepadvances/zpab005
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic fitness and the sleeping brain of adolescents—a pilot study

Abstract: Study Objectives Aerobic fitness (AF) and sleep are major determinants of health in adolescents and impact neurocognitive and psychological development. However, little is known about the interactions between AF and sleep during the developmental transition experienced across adolescence. This study aimed to consider the relationships between AF and habitual sleep patterns and sleep neurophysiology in healthy adolescents. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Insufficient light exposure can disrupt the body's circadian rhythm leading to a loss of synchrony in not only the sleep wake cycle but many other metabolic and homeostatic processes that are influenced heavily by circadian processes (Blume et al, 2019). Physical activity has been shown to promote healthy sleep habits, improve sleep quality and duration in individuals through hormonal, neurological and metabolic mechanisms (Neikrug et al, 2021; Uchida et al, 2012; Wang, 2017). As it is already well established that physical activity effectively aids in the treatment of hypertension and obesity in addition to its positive impact on sleep found in this study, it seems that interventions that increase physical activity may be especially useful in treating insufficient sleep associated cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient light exposure can disrupt the body's circadian rhythm leading to a loss of synchrony in not only the sleep wake cycle but many other metabolic and homeostatic processes that are influenced heavily by circadian processes (Blume et al, 2019). Physical activity has been shown to promote healthy sleep habits, improve sleep quality and duration in individuals through hormonal, neurological and metabolic mechanisms (Neikrug et al, 2021; Uchida et al, 2012; Wang, 2017). As it is already well established that physical activity effectively aids in the treatment of hypertension and obesity in addition to its positive impact on sleep found in this study, it seems that interventions that increase physical activity may be especially useful in treating insufficient sleep associated cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…. Physical activity has been shown to promote healthy sleep habits, improve sleep quality and duration in individuals through hormonal, neurological and metabolic mechanisms(Neikrug et al, 2021;Uchida et al, 2012;Wang, 2017). As it is already well established that physical activity effectively aids in the treatment of T A B L E 3 (Continued)…”
mentioning
confidence: 99%
“…Previously, Myllymäki et al (2011) and Thomas et al (2020) described an increasing trend in N2 sleep stage after evening exercise compared to no exercise. Neikrug et al (2021) stated aerobic fitness is associated with topographically specific elements of sleep physiology (e.g., N2 sleep spindles), which are known to support neuroplasticity and cognitive processes. Thus, pending further research to clarify the relationship between N2 sleep stage and exercise, these findings align with recent evidence suggesting the critical role of NREM sleep after exercise, while we observed that it may be independent of the exercise time.…”
Section: Discussionmentioning
confidence: 99%